Ethnic minority immigrants and their British descendants in the UK labour market: an investigation of Black African and Black Caribbean current employment status in the UK - Scott Foster; Ben George (Cogent Business & Management)
Ethnic minority individuals endure persistent labour market disparity and employment disadvantages, potentially placing them at high risk of employment loss. Despite research efforts to shed light on the adverse outcomes of labour market disparity on these ethnic groups, the issue persists. Our thorough analysis of their experiences and the factors influencing these disadvantages, using human capital and social capital theories, provides crucial insights for understanding and addressing this issue and offers practical interventions. Our data from 32 participants through semi-structured interviews is complemented by secondary sources such as journals. Our findings show that factors such as lack of recognition of foreign qualifications, UK work experience and skills, unequal opportunity for career progression, racism and inadequate social networks contribute to persistent employment disadvantages of these ethnic minority groups. Second-generation ethnic minorities have made progress in the labour market, but ethnic penalties remain.